Risālat iʿtibār an-nāsik fī ḏikr al-āṯār al-karīma wa-'l-manāsik - Ibn-Ǧubair, Muḥammad Ibn-Aḥmad 1145-1217 (Dār al-Amān, 2014)
Muslim pilgrims and pilgrimages; rituals
In arab. Schr., arab.
Includes bibliographical references (p. 113-118)
Keywords: Islam; Wallfahrt